Latin America in the rough waters of the multipolarity of the emerging world order.: Politics and regional geopolitics (2000-2018) - Rocha, Alberto (2019)
Latin America and the Caribbean (LAC) remained linked to the American and Pan- American continental order throughout the bipolar international order, from 1945 to 1990/91. When this bipolar international order fell, due to the implosion of the USSR, the US designed and promoted the Post Cold War unipolar order, which lasted until 2016. LAC, at first, remained articulated to the American and Pan American continental order and, in a second moment, from the end of the nineties, began to distance itself and become autonomous from the USA. Thus, from 2000 until 2015/16, the region was governed mainly by progressive presidents, which allowed it to gain greater autonomy and cohesion. Thanks to an important deployment of its regional integration process, LAC took important steps towards the configuration of a Latin American and Caribbean regional order (articulated to the Asia Pacific), which crystallized in the foundation and start-up of CELAC and the China-CELAC Forum. These 15 years were very important for the region, but, this situation began to change rapidly with the arrival of conservative and neoliberal governments in the region and also with the arrival of D. Trump, a conservative and supremacist government, in the US. This is how the multipolar transition opens towards a new world order. As a result, LAC rearticulates with the American and (neo) Pan-American continental order: geopolitical relations with the US, reactivation of the OAS and relaunch of the Monroe Doctrine. The conservative governments of the region are strenthening their “carnal” relations with the USA. But, in this new geopolitical relationship, the US government only offers weapons and troops to promote invasion of rebel countries. In this new relationship there is no money for cooperation with the countries of the region. So, the geoeconomy of the conservative and neoliberal governments continues its movement towards China and the Asia Pacific. Thus, geopolitics looks towards North America and the US, and geoeconomy flows to the Asia Pacific and China, this may be called a true "schizophrenia".